2006
DOI: 10.1101/gad.385306
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of replication origins in yeast by comparative genomics

Abstract: We discovered that sequences essential for replication origin function are frequently conserved in sensu stricto Saccharomyces species. Here we use analysis of phylogenetic conservation to identify replication origin sequences throughout the Saccharomyces cerevisiae genome at base pair resolution. Origin activity was confirmed for each of 228 predicted sites-representing 86% of apparent origin regions. This is the first study to determine the genome-wide location of replication origins at a resolution sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
226
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(236 citation statements)
references
References 32 publications
6
226
0
2
Order By: Relevance
“…Phylogenetic sequence conservation allowed the precise identification of functional ACS motifs. Although the majority of ACS elements were found to be conserved in at least one other sensu stricto species, we found that only 18% were conserved in the five species investigated (Nieduszynski et al 2006). The lack of sequence conservation could reflect genuine divergence between the species or could be a consequence of limited sequence data, poor sequence alignment, or the definition of sequence conservation.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…Phylogenetic sequence conservation allowed the precise identification of functional ACS motifs. Although the majority of ACS elements were found to be conserved in at least one other sensu stricto species, we found that only 18% were conserved in the five species investigated (Nieduszynski et al 2006). The lack of sequence conservation could reflect genuine divergence between the species or could be a consequence of limited sequence data, poor sequence alignment, or the definition of sequence conservation.…”
Section: Resultsmentioning
confidence: 53%
“…Comparative genomic approaches in the sensu stricto group of Saccharomyces yeasts revealed phylogenetic conservation of the ORC-binding site and facilitated the identification of functional ACS motifs (Theis et al 1999;Nieduszynski et al 2006;Chang et al 2008). Other studies have investigated genome replication in a wider range of Saccharomycotina species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Another study took advantage of the presence of singlestranded DNA at replication forks to map replication origins in budding yeast and in fission yeast (Feng et al 2007). Finally, a comparative analysis of phylogenetic conservation of sequences between five related Saccharomyces species was used to map S. cerevisiae origins at base pair resolution (Nieduszynski et al 2006). These origins appear in OriDB, a web-based catalogue gathering all the genome-wide datasets available for S. cerevisiae (Nieduszynski et al 2007).…”
Section: Dna Replication Programs: the Yeast Paradigmmentioning
confidence: 99%